Depressive mood and sexuality in adolescence - Rosando, Anabela (2013)
The present study aimed to analyse the influence of the psychopathological symptoms, specifically depression within sexuality, through a random sample of 254 adolescents, studying in three secondary schools near Lisbon, with an average age of 16,7 years old (SD=1,48), of which 82 were males and 172 were females. For the data gathering the following instruments were used: a Demographic Questionnaire, a Lifestyle and Youth Beliefs Questionnaire, the Children’s Depression Inventory – CDI (Kovacs, 1981) and the Brief Symptom Inventory – BSI (Derogatis, 1982). Teenagers who have a lower self-esteem and more inter-personal sensibility, tend not to have had sex. Concerning the use of condom, teenagers who do not use condoms presented higher prevalence of psychological symptoms in general, feelings of negative humour, low self-esteem and phobic anxiety.